A capability pedagogy for excluded youth: Fostering recognition and imagining alternative futures. (July 2021) - DeJaeghere, Joan
Out-of-school youth are often characterized as at risk, idle, or troublemakers and are essentially excluded from being citizens of their societies. In Tanzania and Uganda, where this study took place, youth who have not completed their secondary education are excluded from further education and formal work and are often not considered members of their community. This article puts forward capabilities and capability-enhancing pedagogies for formal and non-formal education settings that aim to foster greater inclusion and equality for such youth. Drawing on a 5-year study of youth in Tanzania and Uganda, the article identifies two capabilities, recognition and imagining alternative futures, that can be fostered through educational practices. Educational practices that change unjust social structures and relations are described, illustrating how they go beyond both capabilities that are individually focused, and critical pedagogy's emphasis on raising awareness of social injustices, but not necessarily resulting in social changes.